Resistance training for shoulder complex stabilization - McCurdy, K.; Vela, L. (International Journal of Sports Science and Coaching, 2015)
The purpose of this review is to provide resistance training recommendations to improve shoulder joint stabilization based on shoulder mechanics and mechanisms of injury. The shoulder encounters external axial loading and internal forces from the shoulder musculature that can lead to injury with shoulder stabilization weakness. Training the musculature to stabilize the shoulder increases the likelihood of achieving muscle balance and reducing the risk of injury. The selected exercises and exercise prescriptions are recommended to create this balance to prevent shoulder impingement and injury caused by common axial loading. ABSTRACT FROM AUTHOR